A retrospective cross-sectional analysis of palliative care needs and interventions in patients with cervical cancer in a palliative care unit in Soweto, Johannesburg - Sobekwa, Mfanelo (Industrial Health Research Unit, 2024)
Introduction Cervical cancer is the second most prevalent cancer among women in South Africa. Little published research is available on the pain syndromes associated with cervical cancer and on the specific spiritual issues in patients with cervical cancer. Aim The aim of this study was to describe and provide an analysis of Palliative Care and total pain needs in patients diagnosed with cervical cancer in two Gauteng hospitals. Objectives The objectives were to determine the physical, psycho-social, and spiritual symptom burden of cervical cancer patients and assess for any correlation between a number of these symptoms and other significant variables. Methodology This study was a retrospective data analysis of 138 records of confirmed cervical cancer patients enrolled at the centre for palliative care at Chris Hani Baragwanath Academic Hospital and Sebokeng Regional Hospital. The data was analysed using SPSS version 10. Categorical variables were summarised using cross tabulation and reporting using Pearson Chi-squared test to determine if there were non-random associations between two independent categorical variables. To compare groups, means, and standard deviations with t-tests for normally distributed variables, medians, and interquartile ranges were also used. All the tests were twotailed and a p-value of less than 0.05 was considered statistically significant. The Confidence Intervals (CIs) were calculated at a 95% confidence level. Results The mean age was 50.53 (range 26-84), with 49% being below age 50 and 76% below age 60. A proportion of 41.7% of patients had an ECOG Performance status score of 0-1 which meant that they had no to little impact on the performance of daily activities. The majority of patients' performance was significantly impacted (58.3%) by their illness, bearing an ECOG score of 2 2 P a g e and above. A majority of patients (80%) reported severe to worst pain, with only 10.8% having expressed no pain at all and 2% reporting to have mild pain. The most commonly expressed distressing physical symptoms were lower abdominal pain at 75%, followed by constipation at 48%, and lower back pain at 30%. Just above two-thirds (70%) of the patients were found to be at advanced stage of the disease presenting at FIGO stage III or IV. Iron deficiency anaemia was found to be another significant clinical condition present in 80.6% of patients with a mean haemoglobin of 8.51. The most prevalent comorbid medical condition amongst this group of patients was HIV (52%) with hypertension (36%) as the second most prevalent. The data showed that 93% of the patients considered themselves spiritual, with 86% wanting a stronger connection with God or a higher being. Only 31% felt abandoned by God and 19% by their spiritual community. Further analysis revealed that 67% of patients did not feel that their illness was a punishment from a higher being and just over half of the patients (53%) felt a need to be forgiven by God for past transgressions. 81% of patients expressed a need for spiritual support as part of their clinical care. 92% of patients expressed to be worried about their illness with 87.7% being able to share how they feel with family or friends. 82.6% experienced peace despite their challenges, with only 10.9% not being at peace.93.5% still felt that life was worthwhile despite having cervical cancer. There was a positive correlation between ECOG & worry and ECOG & peace and a negative correlation between ECOG & being able to share. A negative correlation between worry and peace and a positive correlation between being able to share & peace, help for future planning & life worthwhile, information & being able to share and information and peace. Feelings of punishment seem to increase the feeling of being abandoned by a higher being, and a need for a stronger connection to a higher being emerged as a central connecting theme. Conclusion This research study highlighted that, indeed, cervical cancer patients have a number of significant palliative care needs that need to be paid attention to when treating them. These needs are multi-dimensional in nature, and some may be complex. Managing these patients requires an interdisciplinary approach and the involvement of multiple team members (including family) to respond to their needs adequately